Konditionierung von biogenen Energieträgern aus den Produkten der bioliq®-Schnellpyrolyse - Nicoleit, Thomas (KIT Scientific Publishing, 2017)
Within the bioliq®-process, the organic phase of straw pyrolysis condensates can be gasified directly, while the aqueous phase can be mixed with char to form a slurry, which also can be gasified. For production and storage, several mixers and stirrers are examined. Grinding the porous and elongated char particles decelerates sedimentation and also reduces the viscosity. Thus, higher concentrated slurries can be mixed, which leads to higher stability.